Experimental identification of defect-induced destructive breakdown of AlGaN ultraviolet avalanche photodiodes - Fan Yang; Fucheng Yang; Jintong Xu; Xiangyang Li (AIP Advances, 2024)
The issue of destructive breakdown and high dark current in AlGaN ultraviolet avalanche photodiodes has conventionally been attributed to material defects, yet direct evidence supporting this claim has been absent. Examining damaged devices that experienced destructive breakdown revealed an intriguing finding: post-treatment with a potent alkali resulted in the emergence of corrosion pits on the device’s surface. Subsequently, a dry etching process was implemented in the targeted area to eliminate the corrosion pit. Remarkably, the current–voltage measurement subsequent to this treatment showcased a complete restoration of the damaged device’s previous performance. This unequivocally indicates that the destructive breakdown was localized, and the point of punch-through could be precisely identified through the corrosion pit. Consequently, it is now firmly believed that material defects constitute the primary cause of destructive breakdown in these instances.